Selective nitrate recognition by a halogen bonding four station [3]rotaxane molecular shuttle - Barendt, T; Beer, T; Docker, A; Marques, I; Félix, V (Wiley, 2016)
The synthesis of the first halogen bonding [3]rotaxane host system containing a bis-iodo triazolium-bis-naphthalene diimide four station axle component is reported. Proton NMR anion binding titration experiments revealed the halogen bonding rotaxane is selective for nitrate over the more basic acetate, hydrogen carbonate and dihydrogen phosphate oxoanions and chloride, and exhibits enhanced recognition of anions relative to a hydrogen bonding analogue. This elaborate interlocked anion receptor functions via a novel dynamic pincer mechanism where upon nitrate anion binding, both macrocycles shuttle from the naphthalene diimide stations at the periphery of the axle to the central halogen bonding iodo-triazolium station anion recognition sites to form a unique 1:1 stoichiometric nitrate anion–rotaxane sandwich complex. Molecular dynamics simulations carried out on the nitrate and chloride halogen bonding [3]rotaxane complexes corroborate the 1H NMR anion binding results.